Klippel-Feil Syndrome and Sprengel Deformity Combined with an Intraspinal Course of the Left Subclavian Artery and a Bovine Aortic Arch Variant - Floemer, F.; Magerkurth, O.; Jauckus, C.; Lütschg, J.; Schneider, J.F. (American Journal of Neuroradiology, 2008)
SUMMARY: We present a case of Klippel-Feil syndrome and Sprengel deformity with a bovine aortic arch and an aberrant course of the left subclavian artery in a 14-year-old boy. CT and MR imaging of the neck and upper thorax demonstrated a cervical osseous segmentation anomaly, a left common carotid artery originating from the innominate artery, and a left subclavian artery coursing through the intraspinal space at the C6 through T1 level. Possible embryonic mechanisms and clinical significance of this variant are reviewed.